Immunological Changes After Mammary Silicone Implant (Journal of Pharmaceutical Negative Results, 2023)
Objectives To determine whether mammary silicone implanted in human females results in a measurable and significant inflammatory and immunological changes after mammary silicone implant insertion. Background Silicones are widely used materials in many fields of medicine and largely are believed to be biologically inert. However, several reports suggest that silicone products are associated with various complications that may involve inflammatory and immune reactions to silicone or development of systemic autoimmune and connective tissue diseases. In this study, we evaluated the sera of silicone implanted patients to detect inflammatory and immunological response. Methods This was a prospective (Cohort) clinical study that was done for 33 female patients operated for augmentation mammoplasty with silicone implant. Patients were operated at Plastic Surgery Department, Menoufia University Hospitals, from February 2019 to November 2022. All patients were operated for unilateral or bilateral augmentation mammoplasty by insertion of textured or smooth mammary silicone implants, either inserted at sub-mammary or sub-pectoral plane pocket. Single brand of silicone implants were used for all patients at this study (Sebbin, Paris, France). Lab investigations were done by same laboratory. Results In this study we examined serum blood samples of 33 women planning for augmentation mammoplasty by mammary silicone implants to determine whether mammary silicone implanted in human females results in a measurable and significant inflammatory and immunological changes after silicone insertion. The results demonstrated that there was statistically significant elevation of CRP, anti-silicone antibody, anticardiolipin IgG and IgM levels after 6 months post-operatively compared to pre-operatives results. Conclusion The increasing levels of anti-silicone antibody and other antibodies can be useful to physicians and surgeons who wish to assess the integrity of an implant when rupture is suspected. The high specificity of the test suggests that continuous monitoring of anti-silicone antibody levels in implanted patients on a regular schedule could be used as a screening procedure for suspected implant failure. While, to determine any causative association between silicone implants with autoimmune and connective tissue diseases, further long-term studies are recommended.